1997
DOI: 10.1002/(sici)1098-2264(199702)18:2<115::aid-gcc6>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA gains and losses in primary endometrial carcinomas by comparative genomic hybridization

Abstract: Comparative genomic hybridization (CGH) was used in a retrospective analysis of chromosomal imbalances in frozen primary tumor specimens from 14 endometrial carcinoma patients. Chromosome changes were detected in nine cases (64%), and tumor stage and grade tended to parallel the degree of genomic imbalances. Gain of the entire long arm of chromosome I was observed in six cases (43%), three of which displayed only this chromosome change. Other common sites of copy number increases included 8q21 → qter (4 cases)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 31 publications
(59 reference statements)
7
36
0
1
Order By: Relevance
“…Similar findings have been obtained in studies of human embryonic kidney epithelial cells (Zimonjic et al, 2001). Recent comparative genomic hybridization analyses have revealed that fewer chromosomes exhibit genomic alterations in endometrial cancer than in other types of tumors (Sonoda et al, 1997). Such genomic imbalances are rarely observed in endometrial cancers, especially those with defective MMR (Hirasawa et al, 2003); this is consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings have been obtained in studies of human embryonic kidney epithelial cells (Zimonjic et al, 2001). Recent comparative genomic hybridization analyses have revealed that fewer chromosomes exhibit genomic alterations in endometrial cancer than in other types of tumors (Sonoda et al, 1997). Such genomic imbalances are rarely observed in endometrial cancers, especially those with defective MMR (Hirasawa et al, 2003); this is consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
“…The gene encoding eIF3h is located in the long arm of chromosome 8 (specifically, 8q23-24), a region that is frequently amplified in many tumor types (22)(23)(24). For example, gain at 8q has been detected in bladder (25), endometrial (26), ovarian (27), and hepatocellular tumors (28). Although other genes, such as MYC and TRPSI, are also associated with the 8q23-24 region, only the EIF3h gene is consistently overexpressed in breast, prostate, and hepatocellular cancers (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…So far, CGH analysis of 47 endometrioid adenocarcinomas of the endometrium has been reported. 18,28,29 Aberrant CGH profiles were found in 27 carcinomas, mainly comprising cases without MI. 1q and 8q overrepresentations were found to be the most consistent alterations, occurring in 20 out of 27 (74%) and 8 out of 27 (62%) of abnormal cases, respectively.…”
Section: Discussionmentioning
confidence: 99%